Rearing of Adult Green Lacewing, Chrysoperla carnea (Stephens) on Different Artificial Diets in the laboratory - Sumera Balouch,; Aslam Bukero,; Imtiaz Ahmed Nizamani,; Muhammad Ismail Kumbhar,; Lubna Bashir Rajput,; Riaz Ahmed Buriro,; Ali Raza Shah,; Naeem Ahmed Qureshi,; Javaid Ahmed Sheikh,; Shahzad Ali Nahiyoon ,; Zarnain Rajput, (Journal of Basic & Applied Sciences, 2016)
A laboratory study was conducted on rearing of adult Green lacewing, Chrysoperla carnea (Stephens) on different artificial diets. Study was conducted under laboratory conditions at | department of Plant Protection, SAU, Tandojam, Sindh, Pakistan during 2013-14 to determined better artificial diet for mass rearing of adult C. carnea. Six diets containing water:honey:yeast i.e., D1 (20ml:2g:2g), D2 (20ml:4g:2g), D3 (20ml:6g:2g), water:sugar:yeast D4(20ml:2g:2g), D5 (20ml:4g:2g), D6 (20 ml:6g:2g) and two diets containing water:gur:yeast i.e., D7 (20ml:2g:2g), D8(20ml:4g:2g), D9 (20 ml:6g:2g) were tested. The results showed that maximum pre-oviposition period (11.5 ± 3.95 days) recorded, oviposition period (18.0 ± 0.91 days) and post-oviposition period (5.0 ± 0.71 days) was recorded on D4, D9 and D1, respectively. Minimum pre-oviposition period (7.25 ± 0.25 days), oviposition period (5.0 ± 1.73 days) and post-oviposition period (2.5 ± 0.87 days) was recorded on D8, D4, and D7, respectively. The highest fecundity (342.5 ± 89.55 eggs) was recorded on D9, whereas the lowest fecundity (42.5 ± 5.48 eggs) was recorded on D4. The eggs laid by female fed on D4 took lesser time (1.75 ± 0.66 days) to hatch. Maximum larval and pupal longevity was recorded in larvae of adults fed on D9. The adults lived longer for 30.0 ± 0.91 days on D9. The maximum egg hatching (55 %), larval-pupal transformation (45 %) and adults emergence (30 %) was recorded on D9. It is concluded that D9was found the best one for mass rearing of adult C. carnea.